DETERMINANTS OF HAPPINESS OF OLDER MEN AND WOMEN IN SILIGURI, WEST BENGAL - Roy, Sourajit (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Happiness denotes a subjective feeling of living a good life. It is a key to successful aging. The older adults who judge themselves as happy, remain in more advantage position to cope up with age related changes than their counterparts. The feeling of happiness in old age depends on several internal and external factors. In this light the present study has tried to examine the variation of feeling of happiness among older adults on the basis of some selected socio-economic and demographic variables. It is found that the augmentation of age, no income and subjective assessment of poor health significantly reduce the feeling among happiness among men elderly. On the other hand, loss of spouse and separate living from children have a greater impact on feeling of happiness among women older adults. Thus, the present investigation indicates that power dimensions like income or participation in family decision play more vital role in influencing happiness among elderly men, whereas, in case of women elderly.